Investigation on the interactions of lymphoma cells with paclitaxel by Raman spectroscopy. Issue 1 (2011) - Lin Lin, Duo Duo; Lin Lin, Juqiang Juqiang; Wu Wu, Yanan Yanan; Feng Feng, Shangyuan Shangyuan; Li Li, Yongzeng Yongzeng; Yu Yu, Yun Yun; Xi Xi, Gangqin Gangqin; Zeng Zeng, Haishan Haishan; Chen Chen, Rong Rong
Abstract : The single-cell Raman spectra of human Burkitt's lymphoma cells (CA46) including cells treated with different doses of paclitaxel and controls without paclitaxel can be detected by confocal micro-Raman spectroscopy. It shows that the Raman bands at 1094 cm –1 assigned to the symmetric stretching vibration mode of O–P–O in the DNA backbone, 1338 cm –1 and 1578 cm –1 due to adenine and guanine of DNA all decrease in intensity with increasing drug dose. On the contrary, the intensity of peaks at 1257 cm –1 due to characteristic vibration of α -helix of Amide III and 1658 cm –1 due to characteristic vibration of α -helix of Amide I both increases with increasing drug dose. Multivariate statistical methods, such as Principle Components Analysis (PCA) and Linear Discriminant Analysis (LDA) were employed to discriminate normal lymphoma cells (CA46) and cells treated with different doses of paclitaxel. It was found that the sensitivity and specificity of differentiating the treated and untreated cell groups increase with drug doses and approach 100% for the high drug dose, consistent with the perception that the cytotoxicity increases with drug dose. These results suggest that Raman spectroscopy combined with multivariate analysis could become a useful tool for assessing the cytotoxicity of drugs such as paclitaxel on human lymphoma cells.